Energy assessment of a residential building renovated with a novel prefabricated envelope integrating HVAC components. Issue 1 (1st September 2022) - Katsigiannis, E; Gerogiannis, P A; Atsonios, I; Bonou, A; Mandilaras, I; Georgi, A; Papadopoulou, S; Tsoutis, C; Founti, M
Abstract: Off-site prefabrication systems continuously gain attention in the building industry as they combine fast construction with fewer and more sustainable resources as well as minimize disturbance for occupants. In this direction, adaptable off-site prefabricated envelope components with embodied HVAC systems have been developed as an effective renovation solution. They can minimise thermal losses through the envelope while at the same time integrated HVAC systems efficiently maintain indoor thermal comfort conditions. In this study, a "Plug-and-Play" prefabricated envelope component incorporating HVAC systems is examined as a solution for the deep renovation of a typical single-family residence in Berlin, aiming to reach NZEB state. This versatile modular system, called SmartWall, can be installed either to the exterior or the interior side of the external wall, incorporating timber-based frame, boards and insulation, high-performance windows and a slim-type fan coil. The evaluation of this prefabricated system is investigated with respect to its energy performance both at component and building level, as well as its calculated embodied energy. The results indicate a reduction of 89% total primary energy highlighting that NZEB state can be ensured if the SmartWall application is combined with sufficient photovoltaic modules. The climate change potential contribution of such retrofit indicates a significant amount of embodied energy, which is nevertheless counterbalanced by the operational energy savings within the first few years after the implementation.